IMBALANCE IN IL-2 AND IL-4 PRODUCTION AND RECEPTION DURING PROLONGED VIRAL ANTIGENEMIA IN TICK-BORN ENCEPHALITIS - A. P. Zima (SPb RAACI, 2014)
Abastract. The aim of present study was to evaluate a role of certain key immunoregulatory cytokines, IL-2 and IL-4, in development of disturbed intercellular cooperation of immunocytes during long-term antigenemia in tick-borne encephalitis infection. By means of novel immunological and molecular biology testing techniques, an imbalance in production and reception of Th1- and Th2-cytokines (resp., IL-2 and IL-4) by mononuclear leukocytes from peripheral blood towards Th2 response was found in cases of prolonged tick-borne encephalitis viral antigenemia. The study has revealed that, when analyzing effects of IL-4 gene polymorphisms upon predisposition to longer persistence of tick-borne encephalitis virus, there is necessary to observe both promoter allelic variants of IL-4 genes, and polymorphisms of appropriate cytokine receptor genes. (Med. Immunol., vol. 10, N 4-5, pp 389-396).